PENDAMPINGAN MINAT BELAJAR PADA PESERTA DIDIK TAMAN BACA MASYARAKAT (TBM) DI ERA PEMBELAJARAN JARAK JAUH (PPJ) - Irwan Zulkarnain Trisnamansyah; Siti Nurfadilah; Amelia Nuraini Hutasoit; Khaerunnisa Khaerunnisa; Marina Julia Putri (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2020)
Learning is an ongoing process of activity in the context of constructive change in children's behavior. Learning interest is a person's interest in a lesson that encourages him to study and pursue that lesson. Therefore, in this study aims to analyze the strengthening of motivation of children's interest in distance learning. This study used qualitative method and conducted at Saung Baca Kragilan, Gelingseng Village. The result of study showed that world of children is a world of play. Children have a great curiosity about something new. The importance of paying attention to children's interest in learning in participating in learning activities requires the right stimulus. For this reason, in a way that suits the child's growth and development. Community reading gardens regarding the duties and functions of community reading gardens in improving children's learning abilities. Furthemore, that needs to be known that one of the factors that influence children's interest in learning is how a teacher or parent is able to package learning activities that can be a special attraction for children in these learning activities.